The Effect of Differentiated Instruction on the Reading Comprehension Ability of Third-Grade Students at SD Inpres 8 Mamboro - Janatul Huzhlifat; Herlina Herlina; Sisriawan Lapasere; Muhammad Aqil; Muhammad Fasli (Journal of Educational Sciences, 2026)
Reading comprehension is a fundamental skill that enables elementary school students to understand information, construct meaning from texts, and achieve success in various learning areas. Despite its importance, students often display different levels of reading comprehension due to variations in learning readiness, interests, and abilities. This study aimed to investigate the effect of differentiated instruction on the reading comprehension ability of third-grade students at SD Inpres 8 Mamboro. A quantitative approach with a one-group pretest–posttest design was employed. The sample consisted of 30 third-grade students selected through saturated sampling. Data were collected using a validated multiple-choice reading comprehension test, with a Cronbach’s Alpha reliability coefficient of 0.840, indicating high reliability. Descriptive analysis showed that the mean score increased from 73.70 in the pretest to 97.04 in the posttest, demonstrating substantial improvement. Since the data were not normally distributed, the Wilcoxon Signed-Rank Test was applied. The results indicated a significance value of 0.001 (p < 0.05), confirming a significant improvement in students’ reading comprehension after the implementation of differentiated instruction. These findings indicate that differentiated instruction effectively accommodates diverse learning needs, enhances student engagement, and improves reading comprehension skills, making it a valuable instructional approach for elementary school education.